200 Years of Pesantren: Tradition, Reform, and the Institutional Trajectory of Pesantren Tremas - Dwi Ratnasari; Luqyana Azmiya Putri; M Sayyidul Abrori; Naif Daifullah Alsulami (Universitas Pesantren Kh abdul Chalim Mojokerto, 2026)
Pesantren Tremas has endured for more than 200 years. Amid dynamic socio-historical changes, the characteristics of a traditional pesantren remain firmly embedded as its distinctive identity. On this basis, this study aims to explore the traditions, reforms, and institutional trajectory of Pesantren Tremas. The study employs a qualitative, historical case study Design, with the unit of analysis focusing on Pesantren Tremas, an Islamic educational institution that has developed over time. The data were analyzed using a thematic analysis combined with historical analysis to identify the transmission of knowledge and the institutional development processes over a long period. The findings reveal that Pesantren Tremas responds to the challenges of changing times by maintaining consistency in its modes of knowledge transmission, such that this traditional legacy is not merely a form of unreflective repetition, but instead functions as a foundation and framework that ultimately shapes the pesantren’s epistemology. Pesantren Tremas does not exhibit resistance to modernity. Instead, it serves as an example of how a traditional pesantren can endure in an increasingly interconnected era without losing its identity as a salafiyah pesantren. Furthermore, the openness demonstrated by the pesantren represents a form of responsiveness that does not isolate itself from emerging educational systems, whether introduced by the state or driven by broader global developments. This study contributes to the scholarship on Islamic education by offering a historically grounded and conceptually robust account of how traditional pesantren sustain epistemic continuity while engaging institutional change, thereby providing a critical reference for understanding the resilience and adaptability of salafiyah educational institutions in contemporary contexts.